Vrednotenje normativne baze podatkov CONOR.SI s stališča visokošolskih katalogizatorjev / Evaluation of the CONOR.SI authority file from cataloguers' point of view in academic libraries - Urška Zupančič; Marija Petek (Organizacija Znanja)
Authority control is an important part of cataloguing. The Slovene CONOR.SI authority file including authority records for individual and corporate authors, enables among others identification of authors. The purpose of the research was to find out cataloguers’ opinions on its usefulness, its advantages and disadvantages, and how creating authority records for corporate authors was practised. The survey was conducted as an online questionnaire and interview, 73 cataloguers from academic libraries participated. The results showed that the majority of surveyed cataloguers were satisfied with CONOR.SI. The two most important advantages were a faster process of cataloguing and easier determination of authority access points. The most frequently pointed out disadvantages were inaccurate and insufficient data on authors, a large number of namesakes, duplicate records, and errors in records due to cataloguers’ superficiality and complex cataloguing rules. When creating authority records for corporate authors, cataloguers use other authority records, the manual ZNAČKA, the internet, cataloguers’ notes from courses in NUK and IZUM. The findings, inter alia, provide insight into the authority control procedures, primarily into creating records for corporate authors. The research can represent a starting point for improvements and further research.